Visual analytics fundamentals. (LiveLessons (Indianapolis, Ind.), 2023)
Nearly 4 Hours of Video Instruction A Visual Introduction to Visual Analytics Overview: Visual Analytics Fundamentals LiveLessons is a practical, hands-on guide to learning the basics of visual analytics. After you finish the videos you will be able to start building compelling visual data narratives using Tableau 2022. About the Instructor: Lindy Ryan is passionate about telling stories with data. She specializes in translating raw data into insightful stories through carefully curated visuals and engaging narrative frameworks. Lindy teaches courses in visual analytics, data visualization, and product design in the Professional Science Master's program at Rutgers, the State University of New Jersey. She also supports Western State Connecticut's MFA writing program as guest faculty to mentor aspiring writers working in their second genre. Lindy previously taught in the Montclair State University (MSU) Business Analytics program, where she received the MSU Professing Excellence Award, which recognizes professors' teaching excellence, particularly those who inspire and motivate students. She has been a Tableau user since 2012. Lindy is the author of The Visual Imperative: Creating a Culture of Visual Discovery (Elsevier Morgan Kaufmann, 2016) and Visual Data Storytelling with Tableau (Pearson Addison-Wesley, 2018), as well as numerous papers, book chapters, and conference presentations worldwide. Skill Level: Beginner Intermediate Learn How To: Navigate the Tableau interface Understand the role of context in visual analytic storytelling Decide which type of basic chart to use with type of data Use maps to represent data Make good design decisions regarding color, lines, and shapes Prepare your data and storyboard your visualization Use advanced visualization formats Who Should Take This Course: Analysts who need to share the results of their data discovery or analysis Students communicating data for reports or presentations Teachers helping learners (of any age) to cultivate visual data literacy Executives and business managers reporting data-driven results or metrics Journalists giving data the starring role in their editorials Course Requirements: A willingness to learn how to tell stories through data Access to Tableau Desktop (Windows or Mac), version 2022 or higher Lesson Descriptions: Lesson 1: Welcome to Visual Analytics Lesson 1 introduces you to the practice of visual analytics with an overview of the state of the data visualization industry. As a foundation for more in-depth explorations throughout this book, we explore how data visualization and visual data storytelling have become in-demand analytic job skills today. The lesson also explores how the two practices are similar and different, and how both are propelled by new technologies and bigger, more diverse, and more dynamic data. Finally, the role of communication skills within visual analytics is discussed along with a brief look at how academia is supporting the demand for visual analysts today. Lesson 2: The Power of Visual Analytics Memory, retention, and emotion form the bases for experience, all of which work in tandem with our brain's visual processing horsepower. This lesson leverages real-life examples to showcase the power of visual analytics and visual data stories to communicate discoveries and insights hidden in data. We review the role of human cognition in visual analytics; how the brain reacts to inputs of data, stories, and data stories as unique entities; and how we can leverage this power to tell effective data narratives and influence action. Lesson 3: Getting Started with Tableau Application requires an environment for practice as a first step toward efficacy. This lesson shifts the focus from theory to implementation as we briefly explore the different products contained within the Tableau application suite, focusing on the Tableau Desktop 2022 user interface. The lesson covers how to get started with Tableau Desktop, reviews the tool's user interface and basic functionality, and discusses how to connect to data and ensure it is properly prepared for analysis. From here you will be able to move on to the visual analytics process to curate visuals and build data dashboards and stories while building skills and competencies in the market-leading data visualization tool most in demand by today's employers. Lesson 4: Keeping Visual Analytics in Context This lesson describes the importance of understanding data's context and its role in helping visual analysts ask the right questions to build a data narrative framework. You learn about exploratory and explanatory analysis and strategies for successful data storytelling, including narrative flow, considerations for spoken versus written narratives that support visuals, and structures that can support your stories for maximum impact. The lesson also explores helpful techniques in Tableau that guide you in crafting effective data narrative structure and keeping data firmly connected to its context. Lesson 5: Fundamental Data Visualizations This lesson introduces the fundamental charts and graphs used to visually communicate data that are offered on the Tableau Show Me Card. The lesson discusses appropriate use cases for each and get you some hands-on opportunities to create examples in Tableau. You learn techniques to help you assess when to use each visualization type according to the data, how to generate these according to best practices, and helpful considerations for when to avoid certain types of charts. The lesson also explores some of the special features available in Tableau to help you get the most from your visualizations. Lesson 6: Fundamental Maps As a continuation of the previous lesson, this lesson introduces two fundamental types of maps available on the Tableau Show Me Card. Again, we discuss appropriate use cases for each and get hands-on to create examples in Tableau, as well as how to generate these according to best practices, and helpful considerations specifically for mapping data. The lesson also explores some of the special features available in Tableau to help you get the most from your maps. Lesson 7: Design Tips for Curating Visual Analytics This lesson dives into human cognition and visual perception to frame how pre-attentive attributes such as size, color, shape, and position affect the usability and efficacy of visual analytics. We explore best practices for how the design elements can be employed to direct an audience's attention and create a visual hierarchy of components to communicate effectively. Lesson 8: Structuring Analytics for Storytelling This lesson moves beyond the basics of visual analytics to take our first steps in architecting outputs of analysis in visual data dashboards and stories. We'll begin by taking a closer look at how to prepare data in Tableau, utilizing some messy survey data--a common experience for data storytellers--before building data dashboards and stories that incorporate features like filters, annotations, and highlights to present compelling, meaningful, and actionable outcomes of visual analytics. Lesson 9: Beyond Fundamentals: Advanced Visualizations This penultimate lesson explores advanced strategies that go beyond fundamental data visualizations to explore a curated set of advanced data visualizations beyond the Tableau Show Me Card. It covers how to create advanced charts that require additional formatting and calculations, including timelines, Likert scale charts, lollipop charts, and more. Lesson 10: Closing Thoughts You have covered a lot of ground in this series. This final lesson recaps the lessons and emphasizes the main takeaways. It also serves as a resource kit by providing checklists of best practices and practical suggestions for continuing to master outputs of visual analytics. It also discusses additional resources available to support you on this journey. About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more.